2020
DOI: 10.1186/s13075-019-2093-6
|View full text |Cite
|
Sign up to set email alerts
|

Statin-induced anti-HMGCR myopathy: successful therapeutic strategies for corticosteroid-free remission in 55 patients

Abstract: Objective: To describe successful therapeutic strategies in statin-induced anti-HMGCR myopathy. Methods: Retrospective data from a cohort of 55 patients with statin-induced anti-HMGCR myopathy, sequentially stratified by the presence of proximal weakness, early remission, and corticosteroid and IVIG use at treatment induction, were analyzed for optimal successful induction and maintenance of remission strategies. Results: A total of 14 patients achieved remission with a corticosteroid-free induction strategy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 26 publications
5
85
0
1
Order By: Relevance
“…25 In the present study, we describe in-depth 20 patients with seronegative scleromyositis that were identified from a cohort of 340 carefully phenotyped patients with AIM. [16][17][18] SSc skin involvement is often absent in early scleromyositis Knowledge of SSc features included in the 2013 ACR/ EULAR SSc classification criteria is a step towards the early identification of SSc in patients with suspected AIM. However, these criteria put emphasis on the presence of SSc skin involvement, yet this feature was initially absent in almost half (45%) of our scleromyositis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In the present study, we describe in-depth 20 patients with seronegative scleromyositis that were identified from a cohort of 340 carefully phenotyped patients with AIM. [16][17][18] SSc skin involvement is often absent in early scleromyositis Knowledge of SSc features included in the 2013 ACR/ EULAR SSc classification criteria is a step towards the early identification of SSc in patients with suspected AIM. However, these criteria put emphasis on the presence of SSc skin involvement, yet this feature was initially absent in almost half (45%) of our scleromyositis patients.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were identified in a cohort of 340 patients with autoimmune myositis (AIM) at the Centre Hospitalier de l'Université de Montréal (CHUM) and Hôpital du Sacré-Coeur de Montréal (HSCM) (Montréal, Québec, Canada) recruited between 1967 and 2019, as previously described. [16][17][18] Study variables A retrospective medical record review using a standardised protocol was performed to collect clinical data, laboratory and imaging investigations, and muscle biopsy findings, as described previously in detail. 16 17 Objective oropharyngeal dysphagia was defined by an abnormal videofluoroscopic swallowing study and/or the need for percutaneous gastrojejunostomy.…”
Section: Patientsmentioning
confidence: 99%
“…High-dose steroids, IVIG, and immunosuppressive agents such as methotrexate, azathioprine, and rituximab are generally considered acceptable treatment options for IMNM [2,[13][14]. Early and aggressive immunotherapy with at least two agents has improved the prognosis for some patients [2,[6][7]15]. However, those who are positive for either anti-SRP or anti-HMGCR have been shown to have mixed results with steroid monotherapy [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that IVIG may attenuate the autoimmune process, allowing muscle regeneration to outpace muscle destruction, but may not wholly abolish muscle degeneration [5]. More recently, Meyer et al showed that in selective cases, initial induction with triple steroid/IVIG/steroid-sparing agent may be more efficacious than induction with steroids alone [10].…”
Section: Discussionmentioning
confidence: 99%